Development of Antioxidant Jelly Using Tropical Fruits - Aina A. Masri, Aina A. Masri; Fazleen I. A. Bakar, Fazleen I. A. Bakar; Munira. Z. Abidin, Munira. Z. Abidin; Nur H. Malik, Nur H. Malik (2023)
The demand for food products packed with antioxidants has greatly increased in recent years due to the alarming statistics on free radical diseases Therefore, antioxidant jelly was formulated in this study using mango (MJ1), passion fruit (PAJ2) and pineapple (PIJ3) juices as base ingredients. The formulated jellies were evaluated for their phytochemical, physicochemical, sensory and nutritional properties. Initially, a survey to 112 respondents was carried out to determine consumer acceptance on antioxidant jelly. Out of the respondents, 63.4% prefer antioxidant jelly products with multiple fruits. The formulated jellies showed significant difference (p<0.05) in moisture content and pH with the highest moisture content was recorded for PAJ2 at 86.03% while MJ1 recorded the highest pH at 3.86 have sour taste that may not be desirable for all consumers. Antioxidant analysis revealed high levels of DPPH, ABTS, and TPC in MJ1, with 82.78%, 76.95%, and 0.07 mg GAE/g, respectively. Color showed a positive value of L*, a*, b* scale, indicating yellowish red colors of MJ1, PAJ2 and PIJ3 due to the